Methanogenic Fermentation of Benzoate - Nottingham, P. M. (1969)
A methanogenic enrichment culture decomposed small concentrations of (14)C-benzoate to (14)C(4) and (14)CO(2) under stringently anaerobic conditions with or without preceding exposure to benzoate.